PELATIHAN DASAR DETEKSI DINI PERTUMBUHAN DAN PERKEMBANGAN ANAK BAGI GURU RA AL-IKHWAN BANGKALAN - Selvia Nurul Qomari; Enggal Sari Maduratna; Nailufar Firdaus (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2020)
The growth and development of children has increased rapidly at an early age, from 0 to 5 years. This period is often referred to as the "Golden Age" phase. The golden age is a very important period to pay close attention to the growth and development of children so that they can be detected as early as possible if an abnormality occurs. As early as possible, monitoring of growth and development can be carried out by parents themselves at home and teachers at school, especially at the RA/PAUD level. Therefore, RA/PAUD teachers need to be equipped with basic knowledge and skills regarding early detection of child growth and development. Community service activities carried out are in the form of introducing instruments, procedures for using instruments, and how to interpret the results of the examination for early detection of growth and deviations. The instruments introduced include the WHO Z-score curve to assess growth, as well as the Developmental Pre-screening Questionnaire (KPSP). As many as 10 teachers were taught how to measure a child's growth, and conduct developmental screening with KPSP The results of the activity showed that the teacher of RA Al-Ikhwan enthusiastically welcomed the training on early detection of growth and development. Most of the teachers were able to carry out examinations and interpret the results well. However, the method of conducting interviews and the use of screening tools still needs to be improved.